High-Dose Rate Brachytherapy Combined with PD-1 Blockade as a Treatment for Metastatic Adrenocortical Carcinoma – A Single Center Case Series - Schwarzlmueller, Paul; Corradini, Stefanie; Seidensticker, Max; Zimmermann, Petra; Schreiner, Jochen; Maier, Tanja; Triebig, Alexandra; Knösel, Thomas; Pazos, Montserrat; Pfluger, Thomas; Weigand, Isabel; Belka, Claus; Ricke, Jens; Reincke, Martin; Schmidmaier, Ralf; Kroiss, Matthias (Hormone and Metabolic Research, 2023)
The response rate of advanced adrenocortical carcinoma (ACC) to standard chemotherapy with mitotane and etoposide/doxorubicin/cisplatin (EDP-M) is unsatisfactory, and benefit is frequently short lived. Immune checkpoint inhibitors (CPI) have been examined in patient’s refractory to EDP-M, but objective response rates are only approximately 15%. High-dose rate brachytherapy (HDR-BT) is a catheter-based internal radiotherapy and expected to favorably combine with immunotherapies. Here we describe three cases of patients with advanced ACC who were treated with HDR-BT and the CPI pembrolizumab. None of the tumors were positive for established response markers to CPI. All patients were female, had progressed on EDP-M and received external beam radiation therapy for metastatic ACC. Pembrolizumab was initiated 7 or 23 months after brachytherapy in two cases and prior to brachytherapy in one case. Best response of lesions treated with brachytherapy was complete (n=2) or partial response (n=1) that was ongoing at last follow up after 23, 45 and 4 months, respectively. Considering all sites of tumor, response was complete and partial remission in the two patients with brachytherapy prior to pembrolizumab. The third patient developed progressive disease with severe Cushing’s syndrome and died due to COVID-19. Immune-related adverse events of colitis (grade 3), gastroduodenitis (grade 3), pneumonitis (grade 2) and thyroiditis (grade 1) occurred in the two patients with systemic response. HDR-BT controlled metastases locally. Sequential combination with CPI therapy may enhance an abscopal antitumoral effect in non-irradiated metastases in ACC. Systematic studies are required to confirm this preliminary experience and to understand underlying mechanisms.
Keywords: adrenocortical carcinoma, cancer; immune checkpoint blockade; brachytherapy; pembrolizumab; abscopal effect